The effects of different variants of eye-tracking-based feedback of attentional processes during virtual social interactions - Schmidt-Peter, Teresa; Wechsler, Theresa F.; Kroczek, Leon O. H.; Mühlberger, Andreas (Frontiers in Virtual Reality, 2025)
IntroductionEnhanced self-focused attention plays an important role in the maintenance of Social Anxiety Disorder (SAD). Therefore, changing attentional processes is a major target in cognitive behavioral therapy (CBT) and recent approaches apply Virtual Reality (VR) behavioral exercises to change these processes. A promising approach to enhance such VR exposure-based exercises is implementing eye-tracking-based feedback.MethodsThis experimental study investigates which characteristics of gaze-related feedback lead to a positive valence and an increase in focused attention on social stimuli. Additionally, we examine differential effects in low (LSA) vs highly socially anxious (HSA) individuals. Overall, 50 participants, who were grouped into LSA and HSA according to the median split of the SPIN, were instructed to hold eye contact with virtual agents until they received feedback either in the form of a smile, a positive tone, or a praise. Furthermore, the required duration of maintaining eye contact with virtual agents to receive feedback was manipulated. The feedback variants were evaluated during and after the experiment via ratings, and participants’ gaze was measured via eye tracking.ResultsResults revealed that the smile feedback was perceived as more pleasant and elicited more eye contact in a subsequent test phase than the praise, which was associated with higher valence than the tone. In addition, LSA participants rated the social feedback variants (smile, praise) as significantly more pleasant than HSA participants, who showed reduced sensitivity to positive social feedback.DiscussionThese findings suggest that socially rewarding feedback is more effective in LSA individuals and may not generalize to those with high social anxiety. Future research should therefore explore further feedback variants within individuals with SAD to further refine and optimize VR-based attentional interventions for enhanced therapeutic outcomes.